2009
DOI: 10.1007/s11947-009-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of Image Analysis and Artificial Neural Network to Predict Mass Transfer Kinetics and Color Changes of Osmotically Dehydrated Kiwifruit

Abstract: The objectives of this study were to use image analysis and artificial neural network to predict mass transfer kinetics and color changes of osmotically dehydrated kiwifruit slices. Kiwifruits were dehydrated implementing four different sucrose concentrations, at three processing temperatures and during four osmotic time periods. A multilayer neural network was developed by using the operation conditions as inputs to estimate water loss, solid gain, and color changes. It was found that artificial neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(76 citation statements)
references
References 29 publications
2
72
0
2
Order By: Relevance
“…As a result DEI increases. These results are in agreement with those reported by Tylewicz, et al (2010) and Fathi, et al (2011a), who reported that DEI for Hayward kiwifruit slices dried by OD were increased by extend the contact time between kiwifruit and OS. On the other hand, DEI of steamed kiwifruit slices decreased as the immersion period extends.…”
Section: Effect Of Steaming Process On Osmotic Dehydration Of Kiwifrusupporting
confidence: 93%
See 2 more Smart Citations
“…As a result DEI increases. These results are in agreement with those reported by Tylewicz, et al (2010) and Fathi, et al (2011a), who reported that DEI for Hayward kiwifruit slices dried by OD were increased by extend the contact time between kiwifruit and OS. On the other hand, DEI of steamed kiwifruit slices decreased as the immersion period extends.…”
Section: Effect Of Steaming Process On Osmotic Dehydration Of Kiwifrusupporting
confidence: 93%
“…It is a highly nutritional fruit due to its high level of vitamin C and its strong antioxidant capacity because of a wide number of phytonutrients including carotenoids, lutein, phenolics, flavonoids, and chlorophyll (Cassano, et al, 2006). On the other hand, kiwifruit has a very short shelf-life due to its high moisture content which fluctuates between 80 -86% (Fathi, et al, 2011a;Hosseinzadeh, et al, 2013). Therefore it is necessary to dry the fruit to increase its shelf life at room temperature without deteriorations, reduction in weight and volume thereby minimize the cost of packaging, handling and transportation during storage orexport (Maskan, 2001;Senadeera, et al, 2005;Diamante, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this process, occurs water migration from the product to the solution and solid migration from the solution to the product. These migrations have been studied in various fruits and vegetables (Fathi et al, 2011;Mercali et al, 2011;Sutar et al, 2012;Porciuncula et al, 2013;Silva et al, 2014). However, with respect to the green bean, few works on osmotic dehydration and convective drying are found in the literature, despite its importance as a product consumed in most countries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…al. [17] studied ANN to predict the mass transfer kinetics and color changes of osmotically dehydrated kiwifruit slices. Kiwifruits were dehydrated implementing four different sucrose concentrations, at three processing temperatures and during four osmotic time periods.…”
Section: Introductionmentioning
confidence: 99%